1995
DOI: 10.1111/j.1365-2036.1995.tb00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Pantoprazole and omeprazole in the treatment of reflux oesophagitis: a European multicentre study

Abstract: S U M M A R YBackground: Pantoprazole is a new substituted benzimidazole which inhibits gastric H+,K+-ATPase. Methods : In this double-blind, multicentre study, pantoprazole 40 mg once daily was compared with omeprazole 20 mg once daily in the treatment of grade I1 and 111 (Savary-Miller) reflux oesophagitis. Endoscopy was repeated after 4 weeks of treatment, and also after 8 weeks in patients unhealed at 4 weeks. Results: The primary efficacy variable was ulcer healing; after 4 weeks, 81/103 (78.6%) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…However, in this study, the healing rate for 40 mg esomeprazole was significantly higher than that for 20 mg omeprazole only in patients with moderate or severe EE. It is noteworthy that treatment with omeprazole yielded healing rates in this trial that were in the upper range of that reported in the literature (74%-94%) [13][14][15][16][17]. This wide range of reported 8-week EE healing rates with omeprazole is likely due to varying study designs, sample size, EE classification systems, and geographic locations.…”
Section: Discussionmentioning
confidence: 36%
“…However, in this study, the healing rate for 40 mg esomeprazole was significantly higher than that for 20 mg omeprazole only in patients with moderate or severe EE. It is noteworthy that treatment with omeprazole yielded healing rates in this trial that were in the upper range of that reported in the literature (74%-94%) [13][14][15][16][17]. This wide range of reported 8-week EE healing rates with omeprazole is likely due to varying study designs, sample size, EE classification systems, and geographic locations.…”
Section: Discussionmentioning
confidence: 36%
“…Surprisingly, the betweentreatment differences in healing rates were greatest for LA grades A (6.9%) and D (4.4%), which are at opposite ends of the LA classification severity spectrum. The healing rate at week 8 with omeprazole (88.3%) observed in this trial is at the high end of the range of healing rates previously reported (74% to 94%) [12][13][14][15]. This wide range of reported 8-week EE healing rates with omeprazole is likely due to varying study designs, sample size, EE classification systems, and geographic locations or may be related to the wide interpatient variability observed with the agent.…”
Section: Discussionmentioning
confidence: 39%
“…Finally, a study looking at higher doses found no significant benefit in healing when the dose of pantoprazole was increased from 40 to 80 mg [29]. When pantoprazole 40 mg was compared with omeprazole 20 or 40 mg once daily, there were no significant differences in esophagitis healing rates [30][31][32]. In addition, similar healing rates were found when pantoprazole 40 mg was compared with esomeprazole 40 mg [33,34], or lansoprazole 30 mg [35].…”
Section: Clinical Efficacy Esophagitis Healing and Acute Symptom Reliefmentioning
confidence: 63%
“…Asymptomatic elevations in liver enzymes, plasma lipoproteins and blood glucose have also been reported [39,82]. In comparative trials, there were no differences in the tolerability of pantoprazole when compared with omeprazole [30] and lansoprazole [34]. One study suggested the rate of community-acquired pneumonia to be higher in patients on acid-suppressing drugs [83].…”
Section: Safety and Tolerabilitymentioning
confidence: 91%